Models for allocating public venture capital to innovation projects: lessons from a French public agency. (4th April 2006) - Le Bas, Christian; Picard, Fabienne
This paper identifies the variables which structure the analysis carried out in a French public venture capital organisation (ANVAR), which makes decisions regarding the funding of innovation projects at early stages of development. Our observations gathered through the elaboration of cognitive maps, concern the processes and routines used by this organisation in supporting innovation and diffusion of emerging technologies especially information/communication technology and biotechnology. We study in particular the capacity to appropriate rents from innovation, the factors limiting profitability, and the nature of risks (as recommended by Martin and Scott, 2000). In terms of technology management, the main implications are that three managerial tasks are crucial for passing the selection barrier: management of intellectual property assets; management of external relationships of the firm; management of knowledge or human capital.